Family functioning of adolescents with restrictive eating disorders with or without nonsuicidal self‐injury - Riva, Anna; Bizzi, Fabiola; Borgatti, Renato; Mensi, Martina; Charpentier Mora, Simone; Di Guardo, Simona; Nacinovich, Renata (Clinical psychology and psychotherapy, 2024)
Family influence is a crucial factor in the onset and maintenance of eating disorders. Nonsuicidal self‐injury (NSSI) and restrictive eating disorders (REDs) co‐occur in a significant percentage of subjects but family functioning of these families remains underexplored. This study examines the family functioning perceptions of 80 families with adolescents experiencing RED, comparing those with and without NSSI, alongside a control group, utilising the FACES‐IV assessment. The study also aims to compare the triadic (adolescent–mother–father) perception of family functioning in the three groups. The results reveal distinct family dynamics in adolescents with both RED and NSSI, marked by problematic functioning perceptions from all family members and low parental agreement. A further understanding of the family functioning of adolescents with RED with NSSI can help clinicians in defining the treatment setting.